Revisiting the Althusser/E. P. Thompson-Controversy: Towards a Marxist theory of communication. Issue 1 (March 2019) - Fuchs, Christian
This essay revisits the controversy between Louis Althusser's Marxist structuralism and Edward P. Thompson's Marxist humanism. It draws conclusions from this controversy for the foundations of the Marxist theory of communication. The controversy's key disagreements concern the questions of how the economic and the non-economic (the base/superstructure problem), as well as structures and agency are related. Whereas Althusser focuses on articulation and over-determination, Thompson stresses the role of experience in society in general, and class societies in particular. This essay reflects on how both these approaches relate to the role of communication in society and capitalism. Communication is a process in which humans produce and reproduce social relations in manners that mediate not just understanding the world and other humans, but also the dialectic of structure and agency and the dialectic of society's realms. For a Marxist theory of society, also the forgotten meaning of communication as commoning is of crucial importance.